ПЕРСОНАЛІСТСЬКІ КОНЦЕПЦІЇ ОСОБИСТОСТІ У ВІТЧИЗНЯНІЙ ФІЛОСОФІЇ НА ПОЧАТКУ XX СТ. (Педагогіка вищої та середньої школи, 2009)
The author of the article characterizes philosophical principles of personalism and considers the subject of the individual and the personality in the views of the Russian philosophers M. Berdyayev, L. Shestov. Attention is paid to the analysis of "God-seekings" as an important means of self-actualization of the personality when search for God becomes search for one's humanity, the actualization of the new dimensions of one's beingю